Development of fluorescent coating substance for anti- counterfeit of high value seeds - Thiphinkong, D.; Sikhao, P. (International Journal of Agricultural Technology, 2021)
The quality and fluorescence of seed after coating with fluorescent compound on cucumber was investigated. The results showed that the coated seed with all types of fluorescent compound had a fluorescence when examined by using a portable ultraviolet light projector. The coated seed with coating substance mixed with Rhodamine had the clearest fluorescence. All the coated seed with coating substance mixed with fluorescence compound were specifically emissions spectra observed from a spectrofluorophotometer. In addition, there were also not affected germination and germination index of seed. In summary, coating with coating substance mixed with Rhodamine is an effective and convenient to mark any cucumber seed lot for provide identity and other qualifications as well as preventing counterfeiting of seeds